Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/sla.0000000000003248
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Hepatic Artery Infusion Chemotherapy is Associated With Improved Survival Regardless of KRAS Mutation Status in Patients With Resected Colorectal Liver Metastases

Abstract: OBJECTIVE:To investigate the impact of adjuvant hepatic artery infusion (HAI) in relation to KRAS mutational status in patients with resected colorectal cancer liver metastases (CRLM). BACKGROUND:Patients with KRAS-mutated CRLM have worse outcomes after resection. Adjuvant HAI chemotherapy improves overall survival after liver resection. METHODS:Patients with resected CRLM treated at MSKCC with and without adjuvant HAI who had available KRAS status (wild-type, WT; mutated, MUT) were reviewed from a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Of the 10 studies that included patients who underwent liver resection, eight were retrospective cohort studies 6,8,9,12‐16 and two were prospectively maintained databases 10,17 . In total, 3491 patients were incorporated, of which 3115 had known RAS status (1123 with mutated RAS vs 1992 with wild‐type RAS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 10 studies that included patients who underwent liver resection, eight were retrospective cohort studies 6,8,9,12‐16 and two were prospectively maintained databases 10,17 . In total, 3491 patients were incorporated, of which 3115 had known RAS status (1123 with mutated RAS vs 1992 with wild‐type RAS).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 6,8‐10,15‐17 reported data regarding the OS of 2779 patients with known RAS status. Patients with RAS gene mutations were found to have significantly worse OS rates (HR 1.49, 95% CI 1.3‐1.71, P < .001; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have demonstrated that the effect of HAIP chemotherapy is independent of KRAS mutational studies. 18 Other studies demonstrated that RAS mutations are associated with unsalvageable recurrences after initial hepatectomy; this may also apply for subsequent recurrences after curative treatment of recurrent CRLM. 19 However, primary tumor location, which is associated with KRAS mutations, and inferior survival in right-sided patients in previous studies, were included in multivariable analysis in this paper.…”
Section: Discussionmentioning
confidence: 97%
“…On this line, we read with interest the retrospective study published by Gholami et al (5), who recently reported on the utilization of adjuvant HAI in the setting of resected CLM. In particular, they reported how adjuvant HAI was independently associated with improved recurrencefree and overall survival regardless of KRAS mutational status.…”
mentioning
confidence: 99%